Transformasi Pesantren: Model Eko-Religius Pondok Pesantren Annuqayah - Muhammad Hadiatur Rahman; Itaanis Tianah; Ahmad Khairi; Yuliyana Sintiya (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This study aims to describe the strategies and stages implemented by Pondok Pesantren Annuqayah in developing an eco-religious model that integrates Islamic teachings with environmental management. The research utilizes a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and document analysis, and then analyzed using the AGIL theory. The results show that Pondok Pesantren Annuqayah successfully implemented the eco-religious model through the stages of adaptation, goal attainment, integration, and latency. Religious values concerning environmental conservation are integrated into the pesantren's regulations and internalized in the daily lives of the students. However, the main challenge faced is the lack of environmental awareness in the surrounding community. This study concludes that pesantren can play a role as agents of change in environmental issues by combining religious education and environmental awareness. The research suggests increasing community involvement in the eco-religious programs and expanding the replication of this model in other pesantren across Indonesia.